Palynofacies and foraminifera as hidrodynamic indicators of Araguari estuary, Amazon coast, Amapá-Brazil - Ferreira, Danielle Esteves S.; Laut, L. L. M.; Carvalho, M. A.; Santos, V. F.; Figueiredo Jr, A. G. (Anuário do Instituto de Geociências, 2006)
Abstract